Responsiveness of reconfigurable manufacturing system (RMS) scheduling decision to system performance - Abdul Aziz, Faieza; Nawawi, A. M.; Hamzeh, S. R.; Rohidatun, M. W.; Ahmad, Siti Azfanizam (American-Eurasian Network for Scientific Information Publications, 2015)
Background: This paper reviews a research or study on responsiveness of scheduling decision to system performance of reconfigurable manufacturing system (RMS). Many researchers around the globe had intensively looking forward for this kind of manufacturing system over the flexible manufacturing system (FMS) due to the flexibility in capacity and functionality. This paper focuses the method on performance measurement on RMS scheduling. The combination of both scheduling and system performance approaches were translated into a mathematical model for better and more precise analysis. The application of artificial intelligence (AI) in a system modeling indicates the serious intention of industries on RMS application.